2010
DOI: 10.1007/s11214-009-9625-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis and Photolysis of Icy Satellite Surfaces: Experiments and Theory

Abstract: The transport and exchange of material between bodies in the outer solar system is often facilitated by their exposure to ionizing radiation. With this in mind we review the effects of energetic ions, electrons and UV photons on materials present in the outer solar system. We consider radiolysis, photolysis, and sputtering of low temperature solids. Radiolysis and photolysis are the chemistry that follows the bond breaking and ionization produced by incident radiation, producing, e.g., O 2 and H 2 from irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 91 publications
1
51
0
Order By: Relevance
“…Irradiation studies of sulfurbearing ices have found that among the stable irradiation products are long-chained sulfur molecules (e.g., Moore 1984;Cassidy et al 2010), which produce a dark residue and have been interpreted, for example, as the cause of the darkened, intensely red deposits found on Io (Carlson et al 2007). Within the framework of our hypothesis, we propose that the retention of H 2 S on the surface of objects in the outer primordial disk contributed to a significant additional reddening, leading to the VR colors.…”
Section: Surface Radiation Processingmentioning
confidence: 99%
“…Irradiation studies of sulfurbearing ices have found that among the stable irradiation products are long-chained sulfur molecules (e.g., Moore 1984;Cassidy et al 2010), which produce a dark residue and have been interpreted, for example, as the cause of the darkened, intensely red deposits found on Io (Carlson et al 2007). Within the framework of our hypothesis, we propose that the retention of H 2 S on the surface of objects in the outer primordial disk contributed to a significant additional reddening, leading to the VR colors.…”
Section: Surface Radiation Processingmentioning
confidence: 99%
“…The resulting organics which are produced through high energy photon and electron chemistry, include low molecular organic species, several of which are of prebiotic interest, such as HCN and HC 3 N, and higher molecular compounds, tholin-like products (cf. Cassidy et al 2010, this issue). The later probably form the aerosol particles present in the lower parts of the atmosphere.…”
Section: Prebiotic Chemistry In the Atmosphere On The Surface In Thmentioning
confidence: 97%
“…Atmospheric chemistry in Titan allows the continuous transformation of methane and dinitrogen into complex organic compounds from the high atmosphere to the surface (see Coustenis et al 2010, this issue;Cassidy et al 2010, this issue).The recent Cassini data, especially from the INMS and CAPS instruments, indicates that the processes start in the ionosphere (Waite et al 2005(Waite et al , 2007. The resulting organics which are produced through high energy photon and electron chemistry, include low molecular organic species, several of which are of prebiotic interest, such as HCN and HC 3 N, and higher molecular compounds, tholin-like products (cf.…”
Section: Prebiotic Chemistry In the Atmosphere On The Surface In Thmentioning
confidence: 99%
“…The interactions between the Galilean satellites and the plasma of the Jovian magnetosphere lead to local changes in the charged particle populations through either additions of new ions or through changes of the momentum that produce plasma heating or cooling. Plasma-surface interactions at Europa and Ganymede have been shown to generate neutral environments around these moons through either direct ion sputtering or radiolysis, followed by sputtering of the recombined water-dissociation products (Shematovich & Johnson 2001;Shematovich et al 2005;Cassidy et al 2010Cassidy et al , 2013. These exospheres have been demonstrated to be spatially non-uniform (Plainaki et al 2012(Plainaki et al , 2013, depending both on the moons' illumination by the Sun and on Jupiter's magnetospheric plasma properties.…”
Section: Space Weather In the Jovian Systemmentioning
confidence: 99%
“…Indirectly: The impact of energetic ions on an icy satellite surface is followed by the release of surface material to the body's exosphere through direct sputtering and/or radiolysis (for an example of how these release mechanisms work see: Johnson et al 2004;Cassidy et al 2010;Teolis et al 2010;Plainaki et al 2012). The generated exospheres are furthermore subject to loss processes either due to gravity escape and particle sticking to the surface or due to photon or plasma-induced ionization/dissociation of their constituents.…”
Section: Energetic Particle Populationsmentioning
confidence: 99%